Immigration enforcement in the UK: how women experience detention, release and removal - Gerlach, A (2018)
In this dissertation I add nuance to our understanding of the experiences of immigration enforcement by exploring it in terms of the concept of 'dignity.' I draw on interviews with women who were either detained in an Immigration Removal Centre at the point I met them, or had been previously. I used interviews as the main method of data collection and my research spanned three research sites: Yarl’s Wood Removal Centre, The UK community, and Jamaica. I asked the participants about their experiences during and after detention, and for their own interpretations of the concept of dignity. I then used these definitions to make sense of their experiences. Resultingly, two key issues have been addressed in my research: how women subject to immigration control define dignity and the ways that immigration detention undermined it. The experiences of women in this study were characterised by three key violations to their dignity. The first was vilification, where they were made to feel as though they were a threat to UK citizens, and that they were in some way dangerous and untrustworthy. The second was a lack of autonomy. All aspects of immigration enforcement restricted the women in this study from directing their own lives, from the uncertainty of indefinite detention, to their enforced dependence on the government or friends to survive in the community and finally when ultimately expelled from the country. The third was diminishment. Women felt lessened by the interaction between themselves and the Home Office through an apparent lack of care for their individual circumstances. Together, these factors undermined their sense of self worth, self esteem and self respect. My work reinforces existing findings around immigration enforcement that are largely negative. I demonstrate throughout this dissertation that the self-worth of women in my study is deeply affected by their time in immigration detention and by what had happened to them after they left, and that these outcomes were linked to the way in which they were treated in relation to their sense of dignity.